The biosorption potential of Plocamium cartilagineum algal biomass for the elimination of the synthetic dye Cibacron Blue - Motik, Chouaib; Chegdani, Fatima; Blaghen, Mohamed (Aquaculture, Aquarium, Conservation & Legislation, 2022)
The presence of dyes in the textile industry waste presents a problem for the environment, as they are mostly toxic, non-biodegradable and resistant to destruction by conventional physico-chemical treatment methods. Current researches are therefore oriented towards low-cost treatment processes, in particular biological methods, using biosorbent materials such as seaweed. Plocamium cartilagineum (Linnaeus) (P. S. Dixon, 1967) is a red endemic alga that has demonstrated its effectiveness in various fields, with several beneficial effects of its derivatives. The antiviral, antimicrobial, cytotoxic or even acaricidal activities of P. cartilagineum have been the subject of several publications. In this work, the objective is to study and confirm the biosorption potential of the alga for environmental purposes. As a matter of fact, experiments were conducted to investigate the biosorption characteristics of the alga on the removal of a textile dye, the Cibacron Blue, from aqueous solution and demonstrate its potential as a low-cost biosorbent for the treatment of colored water. The effects of temperature, solution pH, biosorbent dosage, biosorbent mass and initial concentration were studied. The results obtained showed that the biosorption of this dye is a rapid phenomenon that is strongly influenced by the pH of the solution. At pH 2 of Cibacron Blue, the maximum fixation capacity of this algal biomass, deduced from the Langmuir model is equal to 25.83 mg g-1. The results suggest that P. cartilagineum could be used as biosorbent for the effective removal of Cibacron Blue in terms of biosorption capacity, availability and low cost.